Efficacy and Safety of Lenalidomide for Treatment of Low-/Intermediate-1-Risk Myelodysplastic Syndromes with or without 5q Deletion: A Systematic Review and Meta-Analysis. - Xin-Yue Lian; Zhi-Hui Zhang; Zhao-Qun Deng; Pin-Fang He; Dong-Ming Yao; Zi-Jun Xu; Xiang-Mei Wen; Lei Yang; Jiang Lin; Jun Qian (PLoS ONE)
Background Lenalidomide could effectively induce red blood cell (RBC) transfusion independence (TI) in patients with lower-risk (Low/Intermediate-1) myelodysplastic syndrome (MDS) with or without 5q deletion. However whether lenalidomide ultimately improves the overall survival (OS) of lower-risk MDS patients and reduces the progression to AML remains controversial. Method A meta-analysis was conducted to examine the efficacy and safety of lenalidomide in the treatment of lower-risk MDS. Efficacy was assessed according to erythroid hematologic response (HI-E), cytogenetic response (CyR), OS and AML progression. Safety was evaluated based on the occurrence rates of grades 3-4 adverse events (AEs). Results Seventeen studies were included consisting of a total of 2160 patients. The analysis indicated that the overall rate of HI-E was 58% with 95% confidence interval (CI) of 43-74%. The pooled estimates for the rates of CyR, complete CyR, and partial CyR were 44% (95% CI 19-68%), 21% (95% CI 13-30%) and 23% (95% CI 15-32%), respectively. The patients with 5q deletion had significantly higher rate of HI-E and CyR than those without 5q deletion (P = 0.002 and 0.001, respectively). The incidences of grades 3-4 neutropenia, thrombocytopenia, leukopenia, anemia, deep vein thrombosis, diarrhea, fatigue and rash were 51% (95% CI 30-73%), 31% (95% CI 20-42%), 9% (95% CI 5-13%), 7% (95% CI 2-12%), 3% (95% CI 2-5%), 3% (95% CI 1-5%), 2% (95% CI 1-4%) and 2% (95% CI 1-3%), respectively. Lenalidomide significantly improved OS (HR: 0.62, 95% CI 0.47-0.83, P = 0.001) and lowered the risk of AML progression in del(5q) patients (RR: 0.61, 95% CI 0.41-0.91, P = 0.014). Conclusions In spite of the AEs, lenalidomide could be effectively and safely used for the treatment of lower-risk MDS patients with or without 5q deletion.